2017
DOI: 10.11594/jtls.07.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Lactate Dehydrogenase and Gamma-Glutamyl Transpeptidase in Breast Cancer Patients receiving Chemotherapy

Abstract: Breast cancer (BC) is the most common type of cancer worldwide, being one of the leading causes of morbidity in the female. In Nepal, it is the second most common type of cancer among women of perimenopausal age group. More than one-quarter of the BC is diagnosed in young Nepalese female, with a familial history of breast cancer, early pregnancy, longer lactation and estrogen exposure, often tumors showing aggressive biological behaviors. Anthracyclines (Doxorubicin) based treatment regime were reported to cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…However, a substantial increase in serum LDH activity was seen between stages II and IV [ 33 ]. The present study findings are in accordance with the Basnyat AS et al study, which reported a significant increase in serum LDH levels with worsening disease severity (stage) [ 34 ]. A research study by Agarwal et al, reported higher serum LDH levels in breast cancer patients than in the control group, with a correlation observed in the clinical stage and size of the tumor, which is consistent with the findings of this research study [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, a substantial increase in serum LDH activity was seen between stages II and IV [ 33 ]. The present study findings are in accordance with the Basnyat AS et al study, which reported a significant increase in serum LDH levels with worsening disease severity (stage) [ 34 ]. A research study by Agarwal et al, reported higher serum LDH levels in breast cancer patients than in the control group, with a correlation observed in the clinical stage and size of the tumor, which is consistent with the findings of this research study [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…7). Present study findings are in accordance with the study conducted by Basnyat AS et al 9 Guddanti Rajeswari et al 10 , in their study, observed serum LDH is significantly increased in Ca breast patients when compared to controls. In the study of Aditi Agarwal et al .…”
Section: Discussionsupporting
confidence: 93%
“…(Fig 3). Present study findings are in accordance with the study Basnyat AS et al 9 , Guddanti Rajeswari et al 10 , Jarari et al 16 Choudhari et al 14 andChandrakanth et al 17-----in their study observed serum GGT levels are significantly increased in Ca breast patients when compared to controls and also observed the further significantly increased levels of GGT (P-value <0.0001) in different stages of Ca breast cases compared to control subjects. In contrast, to present study Guddanti Rajeswari et al 10 , in their study, there is a negative correlation (r-value=-0.2105) of serum GGT with ALP levels in the post-menopausal group of breast cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our result also supported by some study mentions that level of LDHA is elevated in many malignant tumors and is associated with tumor proliferation and malignant growth, with potential implications for tumor diagnosis and therapy and The high activities of LDH in cancer cells may be due to the process of high cell proliferation, migration, or invasion than normal cells [20]. Our study also study revealed, Gamma glutamyl transpeptidase (GGT) were significantly increased only at grade III (p value 0.022) .These observations were in agreement with the studies of Fentiman, et al [21] and McElroy et al [22]. Other study conducted by Basnyat et al, find that LDH and GGT showed steady and progressive increase in the activities of these enzymes from stage I-IV.…”
Section: Discussionsupporting
confidence: 92%